The Manual, Chemical, Cultural, and Integrated Weed Management in Soybean Production (SAARC Journal of Agriculture, 2023)
A field experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka, from December 2021 to April 2022 to study the effect of weed management practices in soybean (Glycine max L.). The experiment was laid out in a Randomized three-Complete Block Design (RCBD) with twelve weed management treatments- no weeding (Control), two hand weeding (at 15 and 30 DAS), pre-emergence herbicide (Herbilin 33% EC @ 400 ml ha-1), post-emergence herbicide Irish EC @ 1200 ml ha-1, pre + post-emergence herbicide, pre-emergence + 1 hand weeding {40 days after sowing (DAS)}, post-emergence herbicide + 1 hand weeding (40 DAS), pre + post-emergence herbicide + 1 hand weeding(40 DAS), straw mulching, intercrop with Amaranthus dubius, and Zea mays, and weed-free. The experimental result showed among seven different weed species found, Cyperus rotundus was the most prevalent weed, with the highest weed density (123 and 128.67 m-2) and relative weed emergence (43.16 and 38.79 %) in the control plot at 30 and 60 DAS. The treatment pre + post-emergence herbicide + 1 hand weeding (40 DAS) showed the longest pod length (4.16 cm) and number of seeds pod-1 (3.89). The weed-free treatment resulted in the highest 1000-seed weight (111.00 g), seed yield (1.86 t ha-1), stover yield (2.16 t ha-1), biological yield (4.03t ha-1), and harvest index (46.35 %). However, the highest benefit-cost ratio (2.85) was obtained under post-emergence herbicide (Irish EC) treatment. Therefore, applying Irish EC was the best broad-spectrum effective herbicide to manage the various weed floras in soybeans for profit.SAARC J. Agric., 21(2): 195-206 (2023)